THE DARKSIDE OF INDIA: THE SOCIOLOGICAL ISSUANCE IN ARAVIND ADIGA’S THE WHITE TIGER AND LAST MAN IN TOWER - Mariappan, B.; Kavitha, M. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The paper focuses on ‘Sociological perspectives in the novels of Aravind Adiga’s The White Tiger (2008) and Last Man in Tower (2011)’. In his novels, he paints a realistic image of modern India. He portrays the social issues concerning poverty, corruption, dishonesty, and degradation of values in the present society. India’s social scenes are depicted as dark side of our modern life which reveals the corruption taking place both in the government and the private sectors are clearly portrays in the novels of Adiga namely The White Tiger and Last Man in Tower. Both the novels deal with the existing reality of the modern scenario of India. Adiga highlights the sociological issues of the contemporary India through his novels. Both novels namely, The White Tiger and Last Man in Tower Aravind Adiga depict the sociological exploitation, bribery, degeneration of values etc. ‘Poverty’ is the primary social problem which portrays in the both novels. In The White Tiger, Balram Halwai the central character of the novel interprets poverty. In Last Man in Tower Adiga represents the poverty as a social problem through the life of people in construction work cities of builders in Bombay through the central character Masterji.